(untitled) (Khairulummah, 2022)
The Quran is an Ocean that has no limits Allah Almighty revealed it to the prophet Muhammad (P.B.U.H) Allah (S.W.T) has promised to save and protect it. The enemies of Quran tried to distort it and make changes in it, but they could not change anything in it. The holy prophet (P.B.U.H) interpreted its verses that were unclear to his companions, and they followed him. Similar was the way of followers of the companions and after them their followers also did the same. One of the Sources, which were consulted by the companions and their follower to interpret the Quran, were people of the book, particularly Abdullah bin Salam and Ka’ab al-Akhbaar and wahab bin Munabeh. From here some of the Stories of the Israelites entered in the interpretations of the Quran especially in the era of the follewers and those who come after them. After the martyrdom of the caliph Othman (may Allah be pleased with him) sprung out differences and conflicts. And the enemies of Islam found an opportunity to fabricate Ahadith. Later, a number of different sects came into being who interpreted the Quran according to their own principles and doctrines. In this way, the amount of the Dakheel increased and engrossed into the interpretations of the Quran. In this paper i have present kinds of interpolation (Al-dakhil) and its causes in the Quranic commentary of Imam al Wahidi Titled al Wasit-fi-Tafsir al-Quran al Majid, This research article is important because Israiliyyat (traditions borrowed from Jews) and fabricated Ahadith that have been interpolated into the Tafsir of Quran is a serious intellectual challenge for the Muslim Ummah and it is duty of Muslim scholars to address this issue on sound academic grounds. This particular scenario has, therefore encouraged me to choose the aforesaid topic for writing my paper